Implementation of entrepreneurship education in the resettlement training program - Nor Hayati, Yahya (2022)
The effectiveness of entrepreneurship program in entrepreneurship education has always been debated in the literature, which opens up the need for an evaluation study. This study evaluates entrepreneurship education’s implementation of the Resettlement Training Program. Context-Input-Process-Product (CIPP), an evaluation model under the System Theory was used as the underpinning theory in this research. The study focuses on input (entrepreneurship training curriculum, role model, and entrepreneurial support), process (students’ orientation, business planning, practical knowledge, and entrepreneurial networking), and product evaluation (entrepreneurial thinking and entrepreneurial interest). A self-administered questionnaire was employed to collect data from 542 respondents. Data were analyzed using multivariate analysis of variance and multiple regression. This study reveals a significant difference in entrepreneurial thinking and entrepreneurial interest of participants trained by the School of Management and Services Sector (BPSPP) and the School of Technical and Vocational (BPTV). Additionally, there is a significant contribution of all input programs towards product programs, namely entrepreneurial thinking and entrepreneurial interest. All process programs also have significant contribution towards entrepreneurial thinking but only three out of four variables in process program have significant contribution towards entrepreneurial interest. Practical knowledge has no relationship with entrepreneurial interest. Entrepreneurial support in the input program and students’ orientation in the process program are the most significant contributors to entrepreneurial thinking and entrepreneurial interest. It is recommended that the implementation process of the entrepreneurship training curriculum, particularly practical knowledge, be reviewed and realigned to improve the product programs, namely entrepreneurial thinking and entrepreneurial interest of participants, thus helping PERHEBAT to produce more entrepreneurs. The implementation of input and process programs of entrepreneurship education in the Resettlement Training Program must be well understood and practiced by all parties involved so as to produce veterans with both high level of entrepreneurial thinking and entrepreneurial interest. Future study may consider to evaluate how respondents’ demographic can contribute to the outcome of entrepreneurship education.